Analisis Penerapan Prinsip First To File Terhadap Perlindungan Hukum Preventif : Studi Atas Sengketa Merek Antara MS GLOW Dan PS GLOW - Nadhila Cahya Nurmalasari; Yudho Taruno Muryanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to examine the application of the first-to-file principle as a preventive legal protection in trademark disputes between MS GLOW and PS GLOW. This legal writing falls under the category of normative legal research, utilizing legislative approaches and case approaches. Legal sources used in this research include primary legal materials and secondary legal materials, collected through document studies and analyzed using deductive legal material analysis with syllogism method. The results of this research indicate that the application of the first-to-file principle as a preventive legal protection in trademark disputes between MS GLOW and PS GLOW is not well implemented and effective. This is due to existing weaknesses both in the substance of the trademark law, namely Law Number 20 of 2016, and in the stages of trademark registration, namely in the announcement stage and the substantive examination stage.